Veronica's Revenge : Contemporary perspectives on photography - Janus, E. (Zurich : Scalo, 1998)
Goldin, Nan ; Frank, Robert ; Man Ray ; Warhol, Andy ; Duchamp, Marcel ; Kelley, Mike ; Wall, Jeff ; Trockel, Rosemarie ; Sherman, Cindy ; Gober, Robert ; Clark, Larry ; Levine, Sherrie ; Orozco, Gabriel ; Boltanski, Christian ; Burgin, Victor ; Prince, Richard ; Leonard, Zoe ; Tillmans, Wolfgang ; Kruger, Barbara ; Clark, Larry ; Calle, Sophie ; Antoni, Janine ; Hatoum, Mona ; Sugimoto Hiroshi ; Matta-Clark, Gordon ; Beuys, Joseph ; Baldessari, John ; Samore, Sam ; Ruff, Thomas ; Becher, Bernd & Hilla ; Fischli & Weiss ; Polke, Sigmar ; Gursky, Andreas ; Richter, Gerhard ; Wearing, Gillian ; Smith, Kiki ; McCarthy, Paul ; Messager, Annette ; Antoni, Janine ; Schütte, Thomas ; Barney, Matthew ; Gilbert & George ; Lucas, Sarah ; Serrano, Andres ; Lawler, Louise ; McCollum, Allan ; Broodthaers, Marcel ; Ray, Charles ; Araki, Nobuyoshi ; Taylor-Wood, Sam ; Horsfield, Craigie ; Dunning, Jeanne ; Fulton, Hamish ; Beecroft, Vanessa ; Lucas, Sarah ; Struth, Thomas ; Gursky, Andreas ; Opie, Catherine ; Armstrong, David ; Clark, Larry ; Wall, Jeff ; Simmons, Laurie ; Förg, Gunther ; Mylaine, Jean-Luc ; Wool, Christopher
boek